Tinjauan Yuridis Pajak Restoran Atas Food Truck - Arga A., Achmad Paku Braja (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
Innovation in the restaurant business is very dynamic, this can be seen in the emergence of the Food Truck business. Food Truck is a new type of business selling food that uses vehicles as a place of sale, so it can move. The definition of restaurant in the restaurant tax regulation does not mention Food Truck, but there are similar concepts so that it has the potential to cause multiple interpretations relating to the understanding of the subject of restaurants and restaurant tax objects. This paper aims to analyze Food Truck from the perspective of tax law as well as specifically related to local taxes.